Muhammadiyah 1 Taman SMA Library Information System - Nouval Aulia Rachman; Ade Eviyanti; Hindarto Hindarto (Procedia of Engineering and Life Science, 2022)
The library is a work unit to store, manage collections of books or other libraries so that many people can use them as sources of information, previously when in the library, if you want to find the desired book or want to borrow books, then you have to look for the books one by one. But now everything has developed rapidly, where with the existence of information technology, everything can be done without having to be complicated. SMA Muhammadiyah 1 Taman is one of the institutions that has not implemented information technology in the library sector, the SMA Muhammadiyah 1 Taman library still uses conventional methods in terms of borrowing books, by writing loans on paper at the back of the book, the problem that often occurs is that the note paper is lost and also books that are lost because of the large number of books, therefore the purpose of this research is to create a system that can facilitate the process of borrowing and returning books and can maintain the availability of existing books. The method used for making the system is the waterfall method and has two stages of testing, alpha and beta. Therefore, a library information system for SMA Muhammadiyah 1 Taman was created which has two roles, members and librarian which can make it easier for librarian to serve students in borrowing books, and students can also find out the availability of the desired book without having to take the book directly into the library rack.